PENGEMBANGAN MEDIA PEMBELAJARAN GAME EDUKASI BERBASIS EDUCAPLAY PADA MATERI WARISAN BUDAYA MUATAN PELAJARAN IPAS KELAS V SD - Made Yoga Prasetya; Komang Surya Adnyana; I Nyoman Pancaria (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to describe the design, analyze the validity, and practicality of the educational Game learning media based on Educaplay. This study aims to produce learning media in the form of educational Games based on Educaplay on cultural heritage material for the fifth grade science subject of SD Negeri 2 Selat which is valid and practical. This study is a Research & Development (R&D) development study using the ADDIE development model. The study was conducted at SD Negeri 2 Selat. Data collection techniques were carried out by observation, interviews, documentation, and questionnaires. The subjects of this study involved three experts in each aspect (media, language, material), 2 teachers, and 7 students. The results of the study showed: (1) The design of the Educational Game media based on Educaplay began with an analysis stage to determine the characteristics and learning needs that occurred in the field, then designing the media which was carried out at the design stage including preparing supporting facilities for making media and making media designs, (2) The validity of the media was in the